PERKEMBANGAN INDUSTRI MIKRO DAN KECIL (STUDI KASUS JAWA BARAT DAN SUMATERA BARAT) - Musthafa, Imelfina; Tan, Firwan (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
This study aims to determine the development of Micro and Small Industries (IMK) in West Java and West Sumatra provinces in terms of the number of IMKs, guidance/training/extension (BPP), partnerships, internet, and marketing. This study utilizes secondary data from the publication “Profile of the Micro and Small Industry Sector” by the Central Statistics Agency of West Java Province and West Sumatra Province for the year 2020. The MSMEs in West Java Province are distributed across 27 cities/regencies, while those in West Sumatra Province are spread across 19 cities/regencies. The analysis employed is descriptive analysis. The results of the study indicate that the development of SMEs in West Java Province has reached 625,943 SMEs, with only 1.65% of SMEs participating in BPP, 0.93% in partnerships, 17.42% using the internet, and only 519 SMEs engaged in international marketing. The development of SMEs in West Sumatra Province, with a total of 94,392 SMEs, also shows that the participation rate in BPP programs remains low at 3.93% of SMEs, partnership at 0.14% of SMEs, internet usage at 11.90% of SMEs, and overseas marketing at only 1,365 SMEs. Government policies to encourage an increase in the number of SMEs need to be implemented through regulations that facilitate SMEs in conducting their businesses. Government policies to encourage SMEs to actively participate in BPP, establish partnerships, and utilize the internet and marketing of products need to be enhanced.